2018
DOI: 10.1002/adbi.201700220
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Actuation of Multifunctional Nanorobotic Platforms to Induce Cancer Cell Death

Abstract: Single‐bath potentiostatic‐pulsed electrodeposition enables the synthesis of bicomponent (i.e., gold and nickel–nickel oxide) multi‐segmented magnetic nanowires that, with extraordinarily low cytotoxicity, are ideal three‐functional medical nanoplatforms because they can transport two types of functional molecules and be magnetically actuated for both controlled targeting and inducing cancer cell death. Alternated segments of Au and Ni–Ni oxide are selected to confer a magnetic character to the nanowires, prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…They observed 24% cell death after an alternating magnetic field of 14 and 35 mT and 20 Hz was applied for 15 min. The segmentation of the NW assisted in tailoring the MR, which in turn decreased the NW agglomeration, and the observed cell death was not induced by magneto-mechanical effect due to the lower MR, but rather it was associated with the NW vibration, which further highlights the association of magnetization and NW behavior [46].…”
Section: The Application Of Magnetic Nanowires As Magnetic Actuation mentioning
confidence: 84%
See 2 more Smart Citations
“…They observed 24% cell death after an alternating magnetic field of 14 and 35 mT and 20 Hz was applied for 15 min. The segmentation of the NW assisted in tailoring the MR, which in turn decreased the NW agglomeration, and the observed cell death was not induced by magneto-mechanical effect due to the lower MR, but rather it was associated with the NW vibration, which further highlights the association of magnetization and NW behavior [46].…”
Section: The Application Of Magnetic Nanowires As Magnetic Actuation mentioning
confidence: 84%
“…Their results suggested that both the mechanical vibration and alternating magnetic field played an active role in the F-actin remodeling and succeeding down-regulation of the audiogenic genes adiponectin AP2 and PPARγ. [46]. This mechanism was later applied to a more cancer therapeutic approach by researchers.…”
Section: The Application Of Magnetic Nanowires As Magnetic Actuation mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the type of fuel, the microstructure, and surface wettability of the MOF surface determine the efficiency of motion. In another study, Serrà et al [91] reported the fabrication of a multifunctional nanorobotic platform with magnetic properties to promote the death of cancer cells by magnetic and mechanical destruction. A multi-segmented nanowire composed by nickel and gold alternating segments was produced by electrodeposition of metals inside the nanochannels of a polycarbonate membrane.…”
Section: Application Of Porphyrins and Hemeproteins In The Constructimentioning
confidence: 99%
“…The nanotubes exhibited ferromagnetism and could be manipulated by a magnet. When the bi-functionalized nanotubes attain cells, magnet or photostimulation can induce cell death that is useful for cancer treatments since the effect of some medical procedures, like hyperthermia and photodynamic therapy, could be improved by application of a rotary magnetic field [91].…”
Section: Application Of Porphyrins and Hemeproteins In The Constructimentioning
confidence: 99%